Common Interest Communities: Standards of Review and Review of Standards - Paula A. Franzese (Washington University Journal of Law & Policy, 2000)
This Essay addresses the propriety of common interest community (CIC) restrictions and governing board decisions rendered with increased frequency in this golden age of “privatization.”
Keywords: Homeowners& #x27; associations; Land use